Influence of crop harvest stages on grain mold incidence in sorghum - B.P. KURUNDKAR, S.D. SOMWANSHI* and (Indian Phytopathology, 2009)
Sorghum grain mold is one of the important limiting factors in cultivation of sorghum hybrids in the rainy season in Marathwada region of Maharashtra state. Present study was conducted for two years i.e. 2002 and 2003 to evaluate new sorghum genotypes received from ICRISAT, Patancheru, Hyderabad for incidence of sorghum grain mold in these thirty eight genotypes as influenced by harvesting stages. Results indicated that, IS-14384 had minimum (13 and 11%) grain mold incidence followed by SGMR-14. Percent moldy grains were minimum (30 and 26%) when harvesting was carried out at physiological maturity of the crop which increased when harvesting was carried out at crop maturity.